Retinopathy of Prematurity in a cohort of neonates at Groote Schuur Hospital - Keraan, Qaunitah (Division of Neonatology, 2016)
Background: Screening for Retinopathy of Prematurity (ROP) is recommended to prevent possible blindness. Prior to 2016, resource limitations precluded routine ROP screening at Groote Schuur Hospital (GSH). Previous pilot studies at GSH did not detect ROP requiring treatment. However, improved survival of very low birth weight infants may affect the prevalence of ROP. Objectives: The study objectives were to: i) Determine the prevalence and severity of ROP in a prospective cohort of premature infants; ii) Describe the association with pre-specified potential risk factors; iii) Assess the feasibility of screening for ROP in our resource-limited setting. Methods Infants with a birth weight of < 1251 g or gestational age < 31 weeks admitted to the GSH neonatal unit from November 2012 to May 2013 were screened. A paediatric ophthalmologist examined the infants at 4 weeks chronological age or 32 weeks corrected gestational age, with follow-up examinations as indicated. Results: Screening was performed in 135 of 191 eligible infants. A total of 313 ROP examinations were performed; 38.5% of infants required a single examination and 16.3% required more than four. The mean gestational age and weight at birth were 30.1 ± 1.9 weeks and 1056 ± 172 g respectively. Seventy-four infants were female (54.8%). Only black (57.0%) and coloured (42.9%) infants were represented. ROP was diagnosed in 40 (29.6%) infants: Eight (5.9%) infants had clinically significant ROP. No infants had stage 4 or 5 ROP. No infants weighing more than 1250 g required treatment. Two infants received laser treatment. Infants with ROP had a lower mean gestational age and lower mean birth weight than those without ROP: 29.2 ± 1.6 vs. 30.5 ± 1.9 weeks (P < 0.002) and 988 ± 181 g vs. 1085 ± 160 g (P = 0.001) respectively. Infants with ROP were more likely to have received a blood transfusion (P < 0.002); to have late onset sepsis (P = 0.024); and to have receive d exclusive breast milk feeds (P = 0.005). There were no significant differences in the level of respiratory support, the need for oxygen therapy, the occurrence of apnoea, early sepsis or severe intraventricular haemorrhage in infants with ROP compared to no ROP. On multivariate analysis, only gestational age was independently associated with ROP was gestational age (RR 0.85; 95% CI 95% 0.740 - 0.988; p=0.03). When gestational age was excluded in post-hoc analysis, birth weight (RR 0.99; 95% CI 0.997 - 0.999; P=0.03) and blood transfusions (RR 1.71; 95% CI 1.0 27 - 2.859; P=0.03) were independently associated with ROP. Infants <1000 g had a 2.5 times higher risk of having ROP than their larger counterparts (95% CI 1.05 - 5.90, P=0.03). ROP screening was completed in 91.1% (123/135) of infants. Conclusion Clinically significant ROP was found in this study. In contrast to previous studies conducted in this setting, two patients received laser treatment. Extensive resources were required for successful screening. The strong association with birth weight and gestational age suggests that infants with lower birth weights and gestational ages should be prioritized for screening in our resource-limited setting.